THE SOCIAL AND EDUCATIONAL SIGNIFICANCE OF APHORISMS: AN ANALYTICAL APPROACH - Jo’raqulova Hurmatoy, (TADQIQOTLAR, 2025)
Annotation: This article examines the social and educational significance of aphorisms. By analyzing 50 well-known aphorisms and surveying students, the study reveals that aphorisms play a crucial role in shaping moral values, promoting civic awareness,  and  encouraging  personal  development.  The  findings  suggest  that aphorisms  are  effective  tools  in  education,  fostering  reflective thinking  and  ethical understanding among young people.